Mutations in GDP-Mannose Pyrophosphorylase B Cause Congenital and Limb-Girdle Muscular Dystrophies Associated with Hypoglycosylation of α-Dystroglycan - Carss, Keren J.; Stevens, Elizabeth; Foley, A. Reghan; Cirak, Sebahattin; Riemersma, Moniek; Torelli, Silvia; Hoischen, Alexander; Willer, Tobias; van Scherpenzeel, Monique; Moore, Steven A.; Messina, Sonia; Bertini, Enrico; et al. (American journal of human genetics, 2013)
Congenital muscular dystrophies with hypoglycosylation of α-dystroglycan (α-DG) are a heterogeneous group of disorders often associated with brain and eye defects in addition to muscular dystrophy. Causative variants in 14 genes thought to be involved in the glycosylation of α-DG have been identified thus far. Allelic mutations in these genes might also cause milder limb-girdle muscular dystrophy phenotypes. Using a combination of exome and Sanger sequencing in eight unrelated individuals, we present evidence that mutations in guanosine diphosphate mannose (GDP-mannose) pyrophosphorylase B (GMPPB) can result in muscular dystrophy variants with hypoglycosylated α-DG. GMPPB catalyzes the formation of GDP-mannose from GTP and mannose-1-phosphate. GDP-mannose is required for O-mannosylation of proteins, including α-DG, and it is the substrate of cytosolic mannosyltransferases. We found reduced α-DG glycosylation in the muscle biopsies of affected individuals and in available fibroblasts. Overexpression of wild-type GMPPB in fibroblasts from an affected individual partially restored glycosylation of α-DG. Whereas wild-type GMPPB localized to the cytoplasm, five of the identified missense mutations caused formation of aggregates in the cytoplasm or near membrane protrusions. Additionally, knockdown of the GMPPB ortholog in zebrafish caused structural muscle defects with decreased motility, eye abnormalities, and reduced glycosylation of α-DG. Together, these data indicate that GMPPB mutations are responsible for congenital and limb-girdle muscular dystrophies with hypoglycosylation of α-DG.